JAVANESE ISLAM DURING MANGKUNEGARA I LEADERSHIP - Septi Anggita Kriskartika; Titis Srimuda Pitana; Susanto Susanto (IBDA` : Jurnal Kajian Islam dan Budaya, 2019)
Religion is the main aspect in constructing a discourse because the Javanese society in the 18th are thickly related with religiosity (Islam) as an inherited principle from the previous king. Mangkunegara I is an influential and interesting figure in the history of Javanese leadership relating to Islam. The medium used in the Islamization process by Mangkunegara I are through art, culture, customs and Islamic religious education. This study aims to show the Javanese Islamic discourse during the leadership of Mangkunegara I in the Babad Kemalon (Pakunegara)/ BK manuscript. The BK manuscript is a Javanese manuscript contains of 30 macapat songs which tells about the struggle of R.M. Said until entitled Mangkunegara I. this research uses the cultural studies paradigm. The theory used is the discourse theory proposed by Michael Foucault. The method used is a qualitative method and the data analysis techniques are done descriptively and interpretatively. This research belongs to library research. The result shows how the leadership of Mangkunegara I was able to show its discourse in Javanese Islam, which was manifested by the way of Mangkunegara I leaderships towards himself, his families, and people. As well as the Islamic base struggle which is always emphasized by Mangkunegara I.